Evaluation of the Thrombolytic and Antioxidant Activity of Leaf Extracts of Plumbago zeylanica L. - Guguloth, Sarvan Kumar; Malothu, Narender; Prasanth, D.S.N.B.K; Areti, Anka Rao (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Plumbago zeylanica L. is one of the extremely accessible conventionally used herbal plants with various biological activities. However, actions of P. zeylanica L on blood clotting and other complications of blood were indisposed therapeutically studied. Therefore, the scope of the current exploration is to screen the thrombolytic, antioxidant, and cytotoxic effects of leaf extracts. Materials and Methods: Thrombolytic activity (in vitro) was assessed with clot lysis and thrombin inhibitory ability. Further, thrombolytic activity (in vivo) was evaluated by a thrombotic tail (carrageenan-induced) animal model. DPPH and nitric oxide (free radical) scavenging methods were employed to check the in vitro antioxidant property. Further cytotoxicity and acute oral toxicity were assessed for plant extract. Results: The quantitative analysis elicits the presence of the magnificent amount of the total phenolic content (96.8±7.92 mg GAE/g) and total flavonoid content (63.52±4.54 mg QE/g) on the dry weight basis. The maximum clot lysis (96.83%±0.657) of methanolic leaf extract was detected in in vitro model at 800 μg/mL in 72 hr. A strong thrombin inhibition (94.63±2.12%) effect was observed for methanol leaf extract at 2 mg/mL. In in vivo studies a significant (p< 0.001) clot lysis was achieved at the tested dose (100, 200 and 300 mg/kg). DPPH radical and nitric oxide scavenging activity showed the IC50 value of 25.47±0.51 and 56.32±0.85, respectively. The methanolic extract was found safer up to the highest lethal dose of 2000 mg/kg. Conclusion: These findings suggested that the plant leaves are comprised of significant thrombolytic properties. It could be a promising source for the existence of antioxidant and thrombolytic agents
Keywords: Plumbago zeylanica L; Thrombolytic activity; Anti-oxidant activity; Cytotoxicity; Streptokinase; DPPH radical etc